2011
DOI: 10.1038/ijo.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of an interdisciplinary 52-week weight loss program for obesity with regard to body weight, comorbidities and quality of life—a prospective study

Abstract: Objectives:To determine the effectiveness of a structured multidisciplinary non-surgical obesity therapy program on the basis of a temporary low-calorie-diet for 12 weeks, and additional intervention modules to enhance nutritional education, to increase physical activity and to modify eating behavior.Design:Prospective multicenter observational study in obese individuals undergoing a medically supervised outpatient-based 52-week treatment in 37 centers in Germany.Subjects:A total of 8296 participants with a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
139
0
43

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 31 publications
9
139
0
43
Order By: Relevance
“…Also Svetkey et al (43) provided similar data in addition to weight change. Lantz et al (41) and Bischoff et al (36) , showed only the changes in body weight and BMI after 2-years observation. Champagne et al (39) presented additionally the changes related to diet by the application of a FFQ.…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 97%
See 4 more Smart Citations
“…Also Svetkey et al (43) provided similar data in addition to weight change. Lantz et al (41) and Bischoff et al (36) , showed only the changes in body weight and BMI after 2-years observation. Champagne et al (39) presented additionally the changes related to diet by the application of a FFQ.…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 97%
“…Champagne et al (39) , Kuller et al (40) and Svetkey et al (43) included also overweight participants. In the weight loss period, all authors (36)(37)(38)(39)(40)(41)(42)(43) applied the reduction of energy intake to at least 5020·8-7531·2 kJ/d (37)(38)(39)(40)42,43) even to very low energy diet (41) and with ready-to-use formula (Optifast) (36) . The content of fat in the diet was taken into account especially by Wadden et al (37) , Milson et al (38) , Kuller et al (40) and Svetkey et al (43).…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 99%
See 3 more Smart Citations